Enhanced uptake in 2D- and 3D- lung cancer cell models of redox responsive PEGylated nanoparticles with sensitivity to reducing extra-and intracellular environments - Conte, Claudia; Mastrotto, Francesca; Taresco, Vincenzo; Tchoryk, Aleksandra; Quaglia, Fabiana; Stolnik, Snjezana; Alexander, Cameron (Elsevier, 2018)
In the treatment of lung cancer, there is an urgent need of innovative medicines to optimize pharmacological responses of conventional chemotherapeutics while attenuating side effects. Here, we have exploited some relatively unexplored subtle differences in reduction potential, associated with cancer cell microenvironments in addition to the well-known changes in intracellular redox environment. We report the synthesis and application of novel redox-responsive PLGA (poly(lactic-co-glycolic acid)) -PEG(polyethylene glycol) nanoparticles (RR-NPs) programmed to change surface properties when entering tumor microenvironments, thus enhance cell internalization of the particles and their drug cargo. The new co-polymers, in which PEG and PLGA were linked by ‘anchiomeric effector’ dithiylethanoate esters were synthesized by a combination of ring-opening polymerization and Michael addition reactions and employed to prepare NPs. Non redox-responsive nanoparticles (nRR-NPs) based on related PLGA-PEG copolymers were also prepared as comparators. Spherical NPs of around 120 nm diameter with a low polydispersity index and negative zeta potentials as well as good drug loading of docetaxel were obtained. The NPs showed prolonged stability in relevant simulated biological fluids and a high ability to penetrate an artificial mucus layer due to the presence of the external PEG coating. Stability, FRET and drug release studies in conditions simulating intracellular reductive environments demonstrated a fast disassembly of the external shell of the NPs, thus triggering on-demand drug release.